Surgical Exposures of the Shoulder. Issue 4 (April 2016) - Chalmers, Peter Nissen; Van Thiel, Geoff S.; Trenhaile, Scott W.
Abstract : Surgical repair, reduction, fixation, and reconstruction for glenohumeral trauma, instability, and degenerative joint disease often require an open surgical exposure. Open shoulder surgery is challenging because the deltoid and rotator cuff musculature envelop the joint, and in most approaches, exposure is limited by the proximity and importance of the axillary nerve. An understanding of the importance of the deltoid and the rotator cuff for glenohumeral function has led to a progression of innovative, advanced, and less invasive approaches to the shoulder. Various advantages, disadvantages, and risks are encountered when performing deltopectoral, deltoid-splitting, and posterior approaches to the glenohumeral joint, with variations of each approach and techniques to extend them and maximize exposure. The ability to perform each of these exposures provides the surgeon with the flexibility to best address the widest variety of pathology.